Analysis of The Influence of Audit Quality, Performance and Auditor’s Emotional Intelligence on Decision Making - Thaib, Azizah Sauri; Pujiati, Herni (Dinasti Publisher, 2025)
Professional accountant services are needed as a guarantee that the financial statements can be trusted as a basis for decision making by internal and external parties. Many factors affect audit reports to be quality, among others, audit quality, auditor's performance and emotional intelligence. Therefore, the purpose of this study is to examine the effect of audit quality, performance and emotional intelligence on decision making. This research is a quantitative research with a descriptive approach. Sample selection using simple random sampling method. The population in this study is the auditors who work at the Public Accountant Office in the Jakarta Region which consists of 9 KAPs who are willing to fill in the questionnaire there are 5 KAPs. From the questionnaire distributed there were 42 respondents who were in accordance with the criteria for determining the sample. The data is collected and analyzed using descriptive statistics, instinct test, class assumption test, multiple regression analysis and hypothesis presentation. The elaboration results above can be concluded that partially audit quality variables, and emotional intelligence have a significant effect on decision making, but performance does not significantly influence decision making. Simultaneously audit quality, performance and emotional intelligence have a significant effect on decision making at the Public Accounting Firm in the Jakarta Region.